High-temperature-resistant ultrasonic coupling agent, preparation method thereof and ultrasonic sensor
Patent Information
- Application Number
- CN202511631694.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-10
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-11-10
AI Technical Summary
然而,传统压电换能器受限于压电陶瓷的居里温度,在大于200℃的高温下易退极化失效,严重制约了超声技术在高温环境下的直接应用
本发明所述超声耦合剂能够在600℃的高温条件下仍保持稳定的声能耦合,使得本发明所述超声传感器能够适用于高温螺栓预紧力的测量、高温环境下平面结构件的无损检测及长时监测。
Smart Images

Figure CN121364252B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of ultrasonic coupling agents and high-temperature nondestructive testing technology, and particularly to a high-temperature resistant ultrasonic coupling agent, its preparation method, and an ultrasonic sensor. Background Technology
[0002] With the rapid development of energy, power, petrochemical, and aerospace industries, equipment operates in extreme environments such as high temperature, high pressure, and strong corrosion for extended periods. Its critical components often face risks of failure such as creep, oxidation corrosion, and thermal fatigue. If the structural health status of the equipment cannot be monitored in real time during operation, sudden failures and safety accidents can easily occur.
[0003] Among numerous non-destructive testing methods, ultrasonic testing is considered a major development direction for high-temperature testing due to its advantages such as high sensitivity, quantitative defect characterization, and strong penetration ability. However, traditional piezoelectric transducers are limited by the Curie temperature of piezoelectric ceramics and are prone to depolarization failure at temperatures above 200°C, severely restricting the direct application of ultrasonic technology in high-temperature environments. Furthermore, the stability of ultrasonic coupling agents at high temperatures is also a major challenge; common organic coupling agents are prone to volatilization and carbonization at high temperatures, leading to a sharp decline in sound energy transmission efficiency.
[0004] Therefore, developing an ultrasonic coupling agent and ultrasonic sensor that can work stably for a long time in high-temperature environments has become a key technology that urgently needs to be mastered in high-temperature nondestructive testing. Summary of the Invention
[0005] To address the above problems, the present invention aims to provide a high-temperature resistant ultrasonic coupling agent, its preparation method, and an ultrasonic sensor.
[0006] The technical solution of the present invention is as follows: In one aspect, a high-temperature resistant ultrasonic coupling agent is provided, comprising, by weight percentage, 40-85% special epoxy resin, 10-50% nano silver powder, 3-10% reactive diluent, 2-8% dispersant, and 2-8% curing agent.
[0007] Preferably, the special epoxy resin is a trifunctional epoxy resin.
[0008] Preferably, the trifunctional epoxy resin is any one or more of triglycidyl-p-aminophenol, tetraglycidyl-diaminodiphenylmethane, and diglycidyl isophthalate.
[0009] Preferably, the particle size of the nano-silver powder is 20-100 nm.
[0010] Preferably, the active diluent is used to adjust the viscosity of the ultrasonic coupling agent to 1000-3000 mPa·s.
[0011] Preferably, the active diluent is any one or more of n-butyl glycidyl ether, allyl glycidyl ether, phenyl glycidyl ether, cresol glycidyl ether, neopentyl glycol diglycidyl ether, and ethylene glycol diglycidyl ether.
[0012] Preferably, the dispersant is a silane coupling agent, which is used to improve the dispersibility of silver nanoparticles in the epoxy system and prevent the silver nanoparticles from agglomerating at high temperatures, thus preventing performance degradation.
[0013] Preferably, the curing agent is any one or more of methyl nadic anhydride, benzophenone tetracarboxylic dianhydride, 4,4′-diaminodiphenyl sulfone, and diaminodiphenylmethane.
[0014] Secondly, a method for preparing the high-temperature resistant ultrasonic coupling agent described in any one of the above claims is also provided, comprising the following steps: S1: Nano silver powder, some special epoxy resin and dispersant are mixed and dispersed under high shear to form a uniform slurry; S2: Add the remaining special epoxy resin to the homogeneous slurry and stir until homogeneous to obtain a precursor solution; S3: Add the reactive diluent to the precursor solution to adjust the viscosity to 1000-3000 mPa·s to obtain a liquid ultrasonic coupling agent; S4: Add the curing agent to the liquid ultrasonic coupling agent and cure to obtain the high-temperature resistant ultrasonic coupling agent.
[0015] Preferably, in step S4, the curing temperature is 150-180℃ and the time is 1-2 hours.
[0016] Thirdly, a high-temperature resistant ultrasonic sensor is also provided, wherein the coupling layer of the ultrasonic sensor is made of the high-temperature resistant ultrasonic coupling agent described in any one of the above claims, or the high-temperature resistant ultrasonic coupling agent prepared by any one of the above claims.
[0017] Preferably, the device includes a housing, which is a cylindrical structure with openings at both the top and bottom. The bottom of the housing is provided with the coupling layer. The upper surface of the coupling layer is provided with a matching layer, a lower electrode, a piezoelectric layer, an upper electrode, and a backing layer in sequence from bottom to top inside the housing. The lower electrode is connected to the housing. The housing serves as a cathode and is connected to an external cable. The upper electrode is connected to the external cable through a wire to form a circuit.
[0018] Preferably, the outer shell is made of brass, the matching layer is made of alumina ceramic, the lower electrode and the upper electrode are both made of high-temperature silver paste, the piezoelectric layer is made of piezoelectric single crystal with a Curie temperature exceeding 1000°C, and the backing layer is made of porous ceramic matrix scatterer.
[0019] Preferably, the high-temperature silver paste is of type 3706, has a silver-gray color, and a viscosity of 25000 mPa·s; the piezoelectric single crystal with a Curie temperature exceeding 1000℃ is a Z-cut lithium niobate single crystal.
[0020] Preferably, the porous ceramic-based scatterer comprises, by weight percentage, 90-98% yttrium-stabilized zirconium oxide powder and 2-10% PMMA pore-forming agent.
[0021] Preferably, the thickness of the matching layer is one-quarter wavelength of the center frequency of the piezoelectric layer; the thickness of the lower electrode and the upper electrode is 3-8 μm; the thickness of the piezoelectric layer is 0.55-0.8 mm, and the center frequency of the piezoelectric layer is 4.5-7.5 MHz; the diameter of the backing layer is 14-15 mm, and the height of the backing layer is 8-15 mm.
[0022] The beneficial effects of this invention are: The ultrasonic coupling agent described in this invention can maintain stable acoustic energy coupling even at a high temperature of 600℃, making the ultrasonic sensor described in this invention suitable for measuring the preload of high-temperature bolts, non-destructive testing of planar structural components in high-temperature environments, and long-term monitoring. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 This is a schematic diagram of the structure of the high-temperature resistant ultrasonic sensor of the present invention; Figure 2 This is a temperature-echo diagram of the high-temperature resistant ultrasonic sensor in Example 1; Figure 3 This is a schematic diagram of the thermal cycling test results of the high-temperature resistant ultrasonic sensor in Example 1, which was conducted at temperatures ranging from 20°C to 600°C. Figure 4 This is a schematic diagram showing the signal stability test results of the high-temperature resistant ultrasonic sensors of Example 1 and Comparative Examples 1-4 at 20℃-600℃.
[0025] Example in the diagram: 1-Coupled layer, 2-Matching layer, 3-Lower electrode, 4-Piezoelectric layer, 5-Upper electrode, 6-Backing layer, 7-Shell, 8-Wire. Detailed Implementation
[0026] The present invention will be further described below with reference to the accompanying drawings and embodiments. It should be noted that, unless otherwise specified, the embodiments and technical features described in this application can be combined with each other. It should also be pointed out that, unless otherwise indicated, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. The terms "comprising" or "including" and similar words used in this invention refer to elements or objects preceding the word that encompass the elements or objects listed following the word and their equivalents, without excluding other elements or objects.
[0027] On one hand, the present invention provides a high-temperature resistant ultrasonic coupling agent, which, by weight percentage, comprises 40-85% special epoxy resin, 10-50% nano silver powder, 3-10% reactive diluent, 2-8% dispersant, and 2-8% curing agent, wherein the special epoxy resin is a trifunctional epoxy resin.
[0028] In this invention, by employing a trifunctional epoxy resin, the ultrasonic coupling agent described herein achieves an optimal balance between temperature resistance and toughness, ensuring long-term stable operation of the coupling layer at 600°C. Furthermore, the ultrasonic coupling agent described herein is in a liquid state before the addition of a curing agent and becomes a solid state after curing with the addition of a curing agent, maintaining stable acoustic-energy coupling even at a high temperature of 600°C.
[0029] In one specific embodiment, the trifunctional epoxy resin is any one or more of triglycidyl-p-aminophenol (TGPAP), tetraglycidyl-diaminodiphenylmethane (TGDDM), and diglycidyl isophthalate (TDE-85). It should be noted that the trifunctional epoxy resin in this embodiment is a preferred trifunctional epoxy resin of the present invention. Other trifunctional epoxy resins in the prior art have similar effects to this embodiment, all enabling the ultrasonic coupling agent of the present invention to achieve the optimal balance between temperature resistance and toughness, ensuring long-term stable operation of the coupling layer at 600℃.
[0030] In one specific embodiment, the nano-silver powder has a particle size of 20-100 nm. In this invention, the addition of nano-silver powder allows for uniform dispersion under the action of a dispersant, improving the conductivity and signal retention rate of the ultrasonic coupling agent. In this embodiment, using nano-silver powder of this particle size effectively enhances the conductivity and acoustic energy retention rate of the ultrasonic coupling agent while preventing agglomeration and sedimentation at high temperatures, thus ensuring performance stability. In one specific embodiment, the reactive diluent is used to adjust the viscosity of the ultrasonic coupling agent to 1000-3000 mPa·s. Optionally, the reactive diluent is any one or more of n-butyl glycidyl ether (BGE), allyl glycidyl ether (AGE), phenyl glycidyl ether (PGE), cresol glycidyl ether (CGE), neopentyl glycol diglycidyl ether (NPGDGE), and ethylene glycol diglycidyl ether (EGDGE).
[0031] In the above embodiments, the present invention adjusts the viscosity of the ultrasonic coupling agent to 1000-3000 mPa·s using an active diluent, which can ensure the continuity of acoustic energy transmission in the coupling layer.
[0032] In one specific embodiment, the dispersant is a silane coupling agent, used to improve the dispersibility of silver nanoparticles in the epoxy system and prevent the agglomeration of silver nanoparticles at high temperatures, which would lead to performance degradation. Optionally, the silane coupling agent is KH550, KH560, etc.
[0033] In one specific embodiment, the curing agent is any one or more of methylnadic anhydride (MNA), benzophenone tetracarboxylic dianhydride (BTDA), 4,4′-diaminodiphenyl sulfone (DDS), and diaminodiphenylmethane (DDM).
[0034] In the above embodiments, the use of the curing agent enables the ultrasonic coupling agent of the present invention to maintain good coupling effect and viscosity even at a high temperature of 600°C.
[0035] Secondly, the present invention also provides a method for preparing the high-temperature resistant ultrasonic coupling agent as described in any one of the above claims, comprising the following steps: S1: Nano silver powder, some special epoxy resin and dispersant are mixed and dispersed under high shear to form a uniform slurry; S2: Add the remaining special epoxy resin to the homogeneous slurry and stir until homogeneous to obtain a precursor solution; S3: Add the reactive diluent to the precursor solution to adjust the viscosity to 1000-3000 mPa·s to obtain a liquid ultrasonic coupling agent; S4: Add the curing agent to the liquid ultrasonic coupling agent and cure to obtain the high-temperature resistant ultrasonic coupling agent.
[0036] In one specific embodiment, the curing temperature is 150-180℃ and the time is 1-2 hours.
[0037] In one specific embodiment using the high-temperature resistant ultrasonic coupling agent described in this invention, a liquid ultrasonic coupling agent is first obtained through steps S1-S3, then a curing agent is added to the liquid ultrasonic coupling agent, stirred and degassed, and then applied to the surface of the detection plane. Finally, the ultrasonic sensor is attached to the object being inspected, and the mixture is heated and cured to form a solid coupling layer.
[0038] Thirdly, the present invention also provides a high-temperature resistant ultrasonic sensor, wherein the coupling layer 1 of the ultrasonic sensor is made of the high-temperature resistant ultrasonic coupling agent described in any one of the above claims, or the high-temperature resistant ultrasonic coupling agent prepared by any one of the above claims.
[0039] In this invention, the high-temperature resistant ultrasonic sensor can achieve efficient excitation and reception of ultrasonic signals in high-temperature environments, which not only solves the high-temperature resistance problem, but also improves acoustic impedance matching and enhances the reliability of ultrasonic detection under extreme conditions.
[0040] In one specific embodiment, the ultrasonic sensor includes a housing 7, which is a cylindrical structure with openings at both the top and bottom. The bottom of the housing 7 is provided with the coupling layer 1. The upper surface of the coupling layer 1 is provided with a matching layer 2, a lower electrode 3, a piezoelectric layer 4, an upper electrode 5, and a backing layer 6 in sequence from bottom to top inside the housing 7. The lower electrode 3 is connected to the housing 7. The housing 7 serves as a cathode and is connected to an external cable. The upper electrode 5 is connected to an external cable through a wire 8 to form a circuit.
[0041] In the above embodiments, the matching layer 2, piezoelectric layer 4, and backing layer 6 achieve acoustic coupling through the lower electrode 3 and the upper electrode 5. The matching material of the matching layer 2 needs to have acoustic impedance matching characteristics, thermal stability, and a certain strength; the piezoelectric material of the piezoelectric layer 4 needs to have a high Curie temperature; and the backing material of the backing layer 6 needs to have a certain acoustic impedance, rigidity, thermal stability, and a high acoustic attenuation coefficient. The lower electrode 3 and the upper electrode 5 need to maintain good conductivity and adhesion strength under high temperature conditions, and the outer shell 7 needs to have high strength and thermal stability.
[0042] In one specific embodiment, the housing 7 is made of brass.
[0043] In one specific embodiment, the matching layer 2 is made of alumina ceramic, and the thickness of the matching layer 2 is one-quarter wavelength of the center frequency of the piezoelectric layer 4, with a coefficient of thermal expansion of (7.5-8.5)×10⁻⁶. -6 / ℃.
[0044] In one specific embodiment, both the lower electrode 3 and the upper electrode 5 are made of high-temperature silver paste, and the thickness of the lower electrode 3 and the upper electrode 5 is 3-8 μm. Optionally, the high-temperature silver paste is of type 3706, silver-gray in color, and has a viscosity of 25000 mPa·s. In this embodiment, the high-temperature silver paste serves not only as an electrode material but also as an adhesive to bond the matching layer 2, the piezoelectric layer 4, and the backing layer 6.
[0045] In one specific embodiment, the piezoelectric layer 4 is made of a piezoelectric single crystal with a Curie temperature exceeding 1000°C. Optionally, the piezoelectric single crystal with a Curie temperature exceeding 1000°C is a Z-cut lithium niobate single crystal. The thickness of the piezoelectric layer 4 is 0.55-0.8 mm, the center frequency of the piezoelectric layer 4 is 4.5-7.5 MHz, and the coefficient of thermal expansion is (7.0-8.0) × 10⁻⁶. -6 / ℃.
[0046] In one specific embodiment, the backing layer 6 is made of a porous ceramic matrix scatterer, the diameter of the backing layer 6 is 14-15 mm, the height of the backing layer 6 is 8-15 mm, and the coefficient of thermal expansion is (8.0-8.5)×10⁻¹⁰. -6 / ℃.
[0047] In one specific embodiment, the porous ceramic-based scatterer comprises, by weight percentage, 90-98% yttrium-stabilized zirconia powder and 2-10% PMMA pore-forming agent. Optionally, the porous ceramic-based scatterer is prepared by the following steps: (1) Mix yttrium-stabilized zirconium oxide powder and PMMA pore-forming agent to form a mixed powder; (2) Pour the mixed powder into the acetone solution in a ventilated place and stir continuously until the acetone solution is completely evaporated and a solid agglomerate is formed; (3) Grind the solid agglomerate into powder in a mortar and pass it through an 80-100 mesh sieve to obtain uniform particles; (4) Place the uniform particles in a cool, dry place for 36-48 hours to dry them, and then press them into a tableting mold to form a preform. (5) The green blank is placed in a muffle furnace and sintered at 1400-1500℃ for 2-3 hours to obtain the porous ceramic matrix scatterer.
[0048] It should be noted that the shell material, matching layer material, lower electrode material, piezoelectric layer material, upper electrode material, and backing layer material used in the above embodiments are all preferred high-temperature resistant materials of the present invention. Other high-temperature resistant shell materials, matching layer materials, lower electrode materials, piezoelectric layer materials, upper electrode materials, and backing layer materials in the prior art can also be applied to the present invention.
[0049] Example 1 A high-temperature resistant ultrasonic sensor, with the following structure: Figure 1 As shown, in this embodiment, the coupling layer of the ultrasonic sensor is made of the high-temperature resistant ultrasonic coupling agent described in this invention. The high-temperature resistant ultrasonic coupling agent, by weight percentage, comprises 60% special epoxy resin (TDE-85), 25% nano-silver powder (particle size 50nm), 8% reactive diluent (AGE + NPGDGE compounded in equal proportions), 2% dispersant (KH550), and 5% curing agent (DDS + MNA compounded in equal proportions). The viscosity before curing is 1500 mPa·s, the curing temperature is 160℃, and the curing time is 2 hours.
[0050] In this embodiment, the outer shell is made of brass; the mating layer is made of alumina ceramic with a thickness of 1 mm and a coefficient of thermal expansion of 8.5 × 10⁻⁶. -6 / ℃; the piezoelectric layer is made of Z-cut lithium niobate single crystal, with a thickness of 0.65mm, a center frequency of 5.6MHz, and a coefficient of thermal expansion of 8.0×10⁻⁶. -6 / ℃; the backing layer is made of porous zirconia ceramic, with a diameter of 14.5mm, a height of 10mm, and a coefficient of thermal expansion of 8.3×10. -6 / ℃; the matching layer, piezoelectric layer and backing layer are acoustically coupled through high-temperature silver paste, forming an upper and lower electrode with a thickness of 5μm. The high-temperature silver paste is of type 3706, silver-gray in color, and has a viscosity of 25000mPa.s. The curing method is as follows: first, heat to 120-150℃ and hold for 10-30min; then place in a tube furnace and heat from room temperature to 800℃ at a rate of 2℃ / min, and hold for 30min; cool to room temperature with the furnace.
[0051] In this embodiment, the porous zirconia ceramic is prepared by the following steps: 30g of yttrium-stabilized zirconia powder and 2g of PMMA pore-forming agent are mixed to form a mixed powder; 100mL of acetone solution is taken, and the mixed powder is poured into the acetone solution in a ventilated place, and stirred continuously until the acetone solution is completely evaporated to form a solid agglomerate; the solid agglomerate is placed in a mortar and ground into powder, and then passed through an 80-100 mesh sieve to form uniform particles; the powder is placed in a cool and dry place for 48 hours to dry; an appropriate amount of the dried uniform powder is placed into a pressing mold and pressed into a blank; the blank is placed in a muffle furnace for high-temperature sintering to produce a porous zirconia backing material.
[0052] During pressing, first compress to 10 MPa at a compression rate of 1 mm / min and hold for 10-30 s; then compress to 55 MPa at a compression rate of 0.5 mm / min and hold for 90-120 s; finally compress to 70 MPa at a compression rate of 0.5 mm / min and hold for 50-90 s. During high-temperature sintering, first raise the temperature from room temperature to 300℃ at a rate of 2℃ / min and hold for 30 min; then raise the temperature from 300℃ to 450℃ at a rate of 0.5℃ / min and hold for 60 min until complete decarburization; then raise the temperature from 450℃ to 1500℃ at a rate of 2℃ / min and hold for 1200 min; then lower the temperature from 1500℃ to 800℃ at a rate of 4℃ / min, and finally cool to room temperature with the furnace.
[0053] Example 2 Unlike Example 1, the special epoxy resin used in the high-temperature resistant ultrasonic coupling agent described in this example is TGPAP.
[0054] Example 3 Unlike Example 1, the special epoxy resin used in the high-temperature resistant ultrasonic coupling agent described in this example is TGDDM.
[0055] Example 4 Unlike Example 1, the active diluent for the high-temperature resistant ultrasonic coupling agent described in this example is PGE.
[0056] Comparative Example 1 Unlike Example 1, the epoxy resin used in the ultrasonic coupling agent of this comparative example is tetraglycidyl diaminodiphenylmethane (TGDDM, tetrafunctional).
[0057] Comparative Example 2 Unlike Example 1, the epoxy resin used in the ultrasonic coupling agent of this comparative example is bisphenol A diglycidyl ether (DGEBA, difunctional).
[0058] Comparative Example 3 Unlike Example 1, no dispersant was added to the ultrasonic coupling agent in this comparative example, and the epoxy resin content was increased to 62%.
[0059] Comparative Example 4 Unlike Example 1, this comparative example does not contain nano-silver powder in its ultrasonic coupling agent, and the epoxy resin content is increased to 85%.
[0060] Test case Performance tests were conducted using the ultrasonic sensors from each embodiment and comparative example. The temperature resistance test results for Example 1 are as follows: Figure 2 As shown. From Figure 2As can be seen, the ultrasonic sensor in Example 1 can work stably for more than 8 hours in a high-temperature environment of 600℃, and its short-term temperature tolerance reaches 800℃; at the same time, the echo signal attenuation is less than 15%; and its temperature resistance performance is excellent.
[0061] Example 1: The ultrasonic sensor underwent 10 thermal cycling tests ranging from 20℃ to 600℃. The test results are as follows: Figure 3 As shown. From Figure 3 As can be seen, the signal remains stable, with signal attenuation less than 10% at the same temperature; thermal stability is good. The absolute bandwidth of the ultrasonic sensor in Example 1 is 5MHz, and the relative bandwidth is close to 100%, demonstrating excellent bandwidth performance. The center frequency of the ultrasonic sensor in Example 1 changes from 5.4MHz to 4.9MHz during the heating process, with a temperature drift of less than 10% at 600℃, indicating good frequency stability.
[0062] The ultrasonic coupling agent of Example 4 has a viscosity of about 3500 mPa·s without the addition of curing agent. After curing, the coupling layer has good temperature resistance, but the coupling effect is slightly inferior to that of the diluent compounded in Example 1.
[0063] The ultrasonic coupling agent in Comparative Example 1 showed a significant increase in viscosity (approximately 6500 mPa·s) without the addition of a curing agent, resulting in poorer leveling and coatability. The cured coupling layer exhibited high hardness and slight brittleness. Its acoustic performance at 600°C was comparable to that of Example 1, but it cracked after three thermal cycles, leading to a sharp drop in signal strength (results are shown in Figure 1). Figure 4 (As shown).
[0064] The ultrasonic coupling agent in Comparative Example 2 had a viscosity of approximately 2000 mPa·s without the addition of a curing agent. After curing, the coupling layer formed began to decompose at 350°C, and the ultrasonic echo signal was completely lost (results are shown below). Figure 4 (As shown).
[0065] In Comparative Example 3, the ultrasonic coupling agent showed uneven dispersion of the silver nanoparticles in the epoxy resin, with silver agglomeration and sedimentation. The resulting coupling agent exhibited inconsistent conductivity and acoustic properties, leading to poor signal stability (results are shown in Figure 3). Figure 4 (As shown).
[0066] The ultrasonic coupling agent in Comparative Example 4 cured into an insulator. The acoustic impedance decreased significantly, resulting in the majority of the ultrasonic waves being reflected. Under the same conditions, the signal strength dropped to less than 50% of that in Example 1 (results are shown below). Figure 4 (As shown).
[0067] It should be noted that the test data of the above embodiments are only test data of some embodiments of the present invention. Ultrasonic coupling agents obtained by changing the type and amount of each raw material of the ultrasonic coupling agent described in the present invention all have similar performance and can maintain stable acoustic energy coupling under high temperature conditions of 600℃. Compared with the prior art, the present invention has significant progress.
[0068] The above description is merely a representative embodiment of the present invention and is not intended to limit the present invention in any way. Any embodiment made by those skilled in the art without departing from the scope of the present invention and utilizing the disclosed technical content is an equivalent embodiment of the present invention. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A high-temperature resistant ultrasonic coupling agent, characterized in that, By weight percentage, it comprises 40-85% special epoxy resin, 10-50% nano silver powder, 3-10% reactive diluent, 2-8% dispersant, and 2-8% curing agent, wherein the special epoxy resin is a trifunctional epoxy resin.
2. The high-temperature resistant ultrasonic coupling agent according to claim 1, characterized in that, The trifunctional epoxy resin is any one or more of triglycidyl-p-aminophenol and diglycidyl isophthalate.
3. The high-temperature resistant ultrasonic coupling agent according to claim 1, characterized in that, The nano-silver powder has a particle size of 20-100 nm, and the active diluent is used to adjust the viscosity of the ultrasonic coupling agent to 1000-3000 mPa·s.
4. The high-temperature resistant ultrasonic coupling agent according to any one of claims 1-3, characterized in that, The active diluent is any one or more of n-butyl glycidyl ether, allyl glycidyl ether, phenyl glycidyl ether, cresol glycidyl ether, neopentyl glycol diglycidyl ether, and ethylene glycol diglycidyl ether. The dispersant is a silane coupling agent, used to improve the dispersibility of silver nanopowder in the epoxy system and prevent the silver nanopowder from agglomerating at high temperatures, which would lead to performance degradation. The curing agent is any one or more of methyl nadic anhydride, benzophenone tetracarboxylic anhydride, 4,4′-diaminodiphenyl sulfone, and diaminodiphenylmethane.
5. The method for preparing the high-temperature resistant ultrasonic coupling agent according to any one of claims 1-4, characterized in that, Includes the following steps: S1: Nano silver powder, some special epoxy resin and dispersant are mixed and dispersed under high shear to form a uniform slurry; S2: Add the remaining special epoxy resin to the homogeneous slurry and stir until homogeneous to obtain a precursor solution; S3: Add the reactive diluent to the precursor solution to adjust the viscosity to 1000-3000 mPa·s to obtain a liquid ultrasonic coupling agent; S4: Add the curing agent to the liquid ultrasonic coupling agent and cure to obtain the high-temperature resistant ultrasonic coupling agent.
6. The method for preparing the high-temperature resistant ultrasonic coupling agent according to claim 5, characterized in that, In step S4, the curing temperature is 150-180℃ and the time is 1-2 hours.
7. A high-temperature resistant ultrasonic sensor, characterized in that, The coupling layer of the ultrasonic sensor is made of the high-temperature resistant ultrasonic coupling agent as described in any one of claims 1-4, or the high-temperature resistant ultrasonic coupling agent prepared by the preparation method described in claim 5 or 6.
8. The high-temperature resistant ultrasonic sensor according to claim 7, characterized in that, The device includes an outer shell, which is a cylindrical structure with openings at both the top and bottom. The bottom of the outer shell is provided with the coupling layer. The upper surface of the coupling layer corresponds to the inner surface of the outer shell, which is provided with a matching layer, a lower electrode, a piezoelectric layer, an upper electrode, and a backing layer from bottom to top. The lower electrode is connected to the outer shell. The outer shell serves as a cathode and is connected to an external cable. The upper electrode is connected to an external cable through a wire to form a circuit.
9. The high-temperature resistant ultrasonic sensor according to claim 8, characterized in that, The outer casing is made of brass; The matching layer is made of alumina ceramic, and the thickness of the matching layer is one-quarter of the wavelength of the center frequency of the piezoelectric layer; Both the lower electrode and the upper electrode are made of high-temperature silver paste, and the thickness of the lower electrode and the upper electrode is 3-8 μm; The piezoelectric layer is made of piezoelectric single crystal with a Curie temperature exceeding 1000℃, the thickness of the piezoelectric layer is 0.55-0.8mm, and the center frequency of the piezoelectric layer is 4.5-7.5MHz; The backing layer is made of a porous ceramic matrix scatterer, the diameter of the backing layer is 14-15mm, and the height of the backing layer is 8-15mm.
10. The high-temperature resistant ultrasonic sensor according to claim 9, characterized in that, The high-temperature silver paste is model 3706, silver-gray in color, and has a viscosity of 25000 mPa·s; the piezoelectric single crystal with a Curie temperature exceeding 1000℃ is a Z-cut lithium niobate single crystal; the porous ceramic matrix scatterer, by weight percentage, comprises 90-98% yttrium oxide-stabilized zirconium oxide powder and 2-10% PMMA pore-forming agent.
Citation Information
Patent Citations
Piezo-electric ultrasonic transducer with conductive bonding agent
JP1987161300A